Strategic Management of the Hospitality Industry in Increasing Innovation and Competitiveness during the Pandemic - Yusuf Iskandar; Martinus Tukiran (Budapest International Research and Critics University, 2022)
This study aims to find suitable strategic management to increase innovation and competitiveness of the hotel industry during the pandemic. This study uses SLR (Systematic Literature Review) articles in the hospitality industry to identify strategic management that can improve innovation and competitiveness of the hospitality industry during the pandemic. By using five appropriate and high-quality journals. The results show that the hotel industry needs to identify the main problems when facing a pandemic and then think of promising innovations by utilizing existing resources within the company.